2015
DOI: 10.23953/cloud.ijarsg.124
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Surface Runoff and Evapotranspiration using SWAT and BEACH for a Tropical Watershed in North Vietnam, Compared to MODIS Products

Abstract: Accurate estimation of surface runoff (Q) and evapotranspiration (ET) is a challenging task but an important research topic because both Q and ET play vital roles in the study of the hydrological cycle, of climate change, water resources, flood management and so on. In this paper we will present the modeling method to estimate the daily Q and ET for a medium-sized watershed in the tropical region of the North of Vietnam using the Soil and Water Assessment Tool (SWAT) and Bridging Event and Continuous Hydrologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
3
6
0
Order By: Relevance
“…Petković et al [44] mentioned that relative humidity and a wind speed of two meters are two factors that play a role in the variation of ET. The same results were also presented by Nguyen and Kappas [3].…”
Section: Procedures Of Model Calibration Using Et-modissupporting
confidence: 85%
See 2 more Smart Citations
“…Petković et al [44] mentioned that relative humidity and a wind speed of two meters are two factors that play a role in the variation of ET. The same results were also presented by Nguyen and Kappas [3].…”
Section: Procedures Of Model Calibration Using Et-modissupporting
confidence: 85%
“…Petković et al [44] mentioned that relative humidity and a wind speed of two meters are two factors that play a role in the variation of ET. The same results were also presented by Nguyen and Kappas [3]. As Figure 8a,b shows, the lowest evapotranspiration is from November to February, when the average temperatures are lower than over the other months.…”
Section: Procedures Of Model Calibration Using Et-modissupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, most of the SWAT studies include analyses of calibration and validation performance results. For example, SWAT model reliability assessments were conducted for the PoKo [162], Cong [148], and Nam Kim [151] watersheds in Vietnam. These studies reported the model performed well for overall streamflow simulation but did not match some peaks and base flows accurately.…”
Section: Example Swat Testing To Support Scenario Analysesmentioning
confidence: 99%
“…Thomas (2015) used RINSPE model implemented in ArcView GIS 3.3 environment to model for estimating runoff in the Olifants river catchment area in north eastern South Africa as surface runoff and entering into the subsurface as infiltration. In another study, Hong Quang Nguyen and Martin Kappas (2015) used Soil and Water Assessment Tool (SWAT) and Bridging Event and Continuous Hydrological (BEACH) models for estimating surface runoff and evapotranspiration in a tropical watershed in North Vietnam. While estimating the runoff in Vindhyachal region, part of Mirzapur district, Uttar Pradesh, northern India, Topno et al (2015) observed an improvement in estimated runoff accuracies by using a curve number (CN) model developed by the United States Department of Agriculture (USDA).…”
Section: Role Of Remote Sensing and Gismentioning
confidence: 99%